Increasing the volume of Gold Open Access journals in SSHA - Halse, Rolf; Linge, Lena-Cecilie (Septentrio Conference Series, 2019)
Currently, there is an apparent lack of Gold Open Access journals in Social Science, Humanities and Arts (SSHA), as showcased by the open letter the Directory of Open Access Journals (DOAJ) sent to the SSHA communities 16 May 2019. DOAJ asserts in the letter that they agree 100% that DOAJ’s coverage of SSHA journals is insufficient. The implications of the lack of available outlets for research articles by SSHA grantholders in the early years of Plan S implementation may include disadvantages for researchers in the fields. A mandatory criterion for Plan S compliant OA journals is that they must be registered in the DOAJ. One consequence of the lack of coverage is when SSHA scholars seek funding from any of the research agencies or funders that are part of cOAlition S, as scholars will encounter difficulties in finding relevant quality Gold OA journals in which they can publish their research. This could impair SSHA scholars’ chances of receiving grants. Because of the ongoing and accelerated changes to the scholarly publication landscape today, there is a need to support SSHA communities with identifying quality journals which qualifies as Gold OA. To achieve ‘true’ Gold OA status a journal needs to be indexed in DOAJ, as Gold OA journals are in practice defined by their inclusion in this directory. The European Reference Index for the Humanities and the Social Sciences (ERIH PLUS) provides a curated register of peer reviewed journals in the social sciences, arts and humanities. Today ERIH PLUS includes 7,473 scientific journals, and 2,220 of the journals are also listed by DOAJ. Furthermore, ERIH PLUS covers 1,469,204 scholarly Gold OA publications, according to data from Dimensions. However, less than half of these, 712,135 publications, are today indexed in DOAJ. Dimensions (free version) classifies Gold OA publications in the following way: “Gold – refers to articles in fully accessible open access journals that are available immediately upon publication without a license”. In this project we seek to identify DOAJ inclusion candidates from the group of journals that have published the 757,069 Gold OA publications that are not listed in DOAJ, according to Dimensions data. We will work with editors/editorial staff of journals that we identify as having the potential to be indexed by DOAJ. The goal is to increase the volume of Gold OA journals in SSHA. We will contact, present arguments and provide support to journal editors in order to convince them to apply for inclusion in DOAJ. In the poster, we will outline and describe some of the key tasks for the project in order to reach our goal. The project that we will briefly outline will center on: Describing incentives for obtaining ‘true’ Gold OA status for SSHA journals Identifying journals in ERIH PLUS for possible DOAJ inclusion Efforts to flip SSHA journals to ‘true’ Gold OA